Predictions of the Effect of Non-Homogeneous Ocean Bubbles on Sound Propagation - Yuezhu Cheng; Jie Shi; Yuan Cao; Haoyang Zhang (Journal of Marine Science and Engineering)
In the ocean, bubbles rarely appear alone and are often not evenly distributed, which makes it complicated to predict the effect of ocean bubbles on sound propagation. To solve this problem, researchers have tried to use approximations such as equivalent and multiple scattering models, but these approximations are accompanied by large errors. Therefore, we propose a semi-numerical and semi-analytical calculation method for underwater sound fields containing non-homogeneous bubbles in this paper. Based on the attenuation cross section and scattering cross section of a single bubble, the non-homogeneous medium is divided into multiple layers of uniform medium. Each layer of the bubble group is regarded as a whole, which can fully reflect the influence of bubble group vibration and scattering on sound wave propagation and is conducive to faster calculation of the sound field of non-homogeneous bubbly liquids. Compared with the classic coupling model, the calculation process of this method is simpler and faster, which solves the problem of fast calculation of sound fields in bubbly liquids and simulation of distributed bubble groups containing non-homogeneous distributed bubbles.